Syntheses and properties of thienyl-substituted dithienophenazines - Meyer, Annemarie; Sigmund, Eva; Luppertz, Friedhelm; Schnakenburg, Gregor; Gadaczek, Immanuel; Bredow, Thomas; Jester, Stefan-S.; Höger, Sigurd (Beilstein Journal of Organic Chemistry, 2010)
A series of dithienophenazines with different lengths of the oligomeric thiophene units (quaterthiophenes and sexithiophenes) was synthesized. The thiophene and phenazine units act as electron donors and acceptors, respectively, resulting in characteristic absorption spectra. The optical spectra were calculated using time-dependent density functional theory at the B3LYP/TZVP level and verify the experimental data. Adsorption of the dithienophenazines on highly ordered pyrolytic graphite (HOPG) was investigated by scanning tunneling microscopy, showing that one of the compounds forms highly organized self-assembled monolayers.
Keywords: oligothiophenes; phenazines; scanning tunneling microscopy; self-assembled monolayers; TD-DFT calculations